Lesson well learnt - Haq, Roohi (Pakistan : Paramount (Pvt.) Ltd., 2025)
Teaching values in the classroom Traditionally, teaching values and social skills has been left to parents; becoming incumbent on teachers to teach these skills. As children grow up they need to learn many lessons about relationships personal integrity, courage and compassion and stories provide the context and link to real life for students to learn these values. Stories and tables being a very powerful medium for learning are the oldest form of education and have been used by human beings to pass down their cultural values and beliefs since time immemorial. Every country, therefore, has its own folklore that carries messages aimed at reforming society and differentiating between right and wrong.
Keywords: English - Fiction Book